Anticipation of the ITE Law and Reconciliation of Its Forms Freedom of Expression through the E-Hights Website - Wita Setyaningrum; Aimee Cepee Morana; Khusnul Nur Vaizi; Retno Damarina; Son Ali Akbar; Sakti Oktasari (Universitas Ahmad Dahlan, 2022)
Introduction to The Problem: Misinterpretation in the application of the Electronic Information and Transaction Law (ITE) can reduce democracy and undermine law enforcement in Indonesia. The complexity of the problems related to the Electronic Information and Transaction Law requires solutions to prevent and prevent problems with the Electronic Information and Transaction Law.Departing from the problems posed by the Electronic Information and Transaction Law, Indonesian still need a lot of work to overcome a degrading freedom of expression. We proposed the renewal by making a conceptual design and prototype, namely the E-Hights (Electronic Human Rights) application to overcome those problems.Purpose/Objective Study: This study is to examine the relationship between the constitution and laws and regulations governing freedom of expression through social media, as well as to examine how the use of a website-based application called E-Hights (Electronic Human Rights) guarantees the implementation of this freedom. expression while minimizing violations of laws governing electronic information and transactions.Design/Methodology/Approach: This research is normative legal research supported by secondary data in the form of primary and secondary legal materials.Findings: There are not a few problems in the implementation of the Electronic Information and Transaction Law, the existence of a rubber article in the Electronic Information and Transaction Law which creates multiple interpretations in law enforcement in Indonesia. This multi-interpretation rubber article has an impact on people's freedom of expression. According to research by the Indonesian Judicial Research Institute, the Electronic Information and Transaction Law is a tool to silence freedom of expression. Thus, this can affect democracy in Indonesia, or it could be said that the Electronic Information and Transaction Law makes people afraid to voice their aspirations to the special government. Therefore, the authors offer a solution that is realized in a web-based application.Paper Type: Research Article or General Review.